P229 Breath-taking outcomes: evaluation of a specialist breathlessness clinic. (15th November 2016) - Douglas, L; English, A; Obita, GP; Hart, SP; Crooks, MG
Abstract : Background: Breathlessness is distressing for patients and is a common reason for emergency department attendance. Chronic refractory breathlessness is associated with anxiety, embarrassment and fear, and effective management is essential to improve quality of life and reduce hospital admissions. 1 Interventions such as breathing control, activity pacing and anxiety management are beneficial. 2 This study examined the effect of attending a dedicated respiratory physiotherapist led breathlessness service on patient reported outcomes. Method: Patients attending the breathlessness clinic between April 2015 and April 2016 completed Numerical Rating Scales (NRS) out of 10 to grade their breathlessness. Data were collected before and 1–2 weeks after clinic attendance. Lower NRS scores represented a lower symptom burden. A change of 1 or more on the NRS was considered clinically significant. Responses were compared using t-tests and Wilcoxon signed-rank tests. Data are presented as mean ± SD. Results: Fifty-two patients attended the breathless clinic during the study period (mean age 73, range 49–92 years). Patients had a range of diagnoses causing their breathlessness with idiopathic pulmonary fibrosis (44.2%), lung cancer (19.2%), and non-specified interstitial lung disease (11.5%) being most common. Significant improvements were observed across all domains. Average breathlessness experienced in the past 24 hours reduced from 3.9 ± 1.7 to 3.6 ± 1.6 (p = 0.001). The worst breathlessness experienced in the past 24 hours reduced by 1 point to 6.3 ± 1.9 (p < 0.001). The distress experienced from breathlessness reduced from 5.8 ± 6.4 to 4.8 ± 4.8 (p < 0.001). Patients' perceived ability to cope with their breathlessness improved by 1 point (p < 0.001). Conclusions: A specialist breathlessness clinic provided a valuable service for patients with chronic refractory breathlessness. Significant, clinically meaningful benefits were observed in terms of the severity of breathlessness that patients experienced. Furthermore, patients perceived a reduction in distress and increased ability to cope. References: Ekström M, Abernethy A, Currow D. The management of chronic breathlessness in patients with advanced and terminal illness. BMJ 2015;349 :g7617. Higginson IJ, Bausewein C, Reilly C, et al . An integrated palliative and respiratory care service for patients with advanced disease and refractory breathlessness: a randomised controlled trial. Lancet Respiratory Medicine2014;2:979–87.